The Influence of the Quality of Digital Population Identity (IKD) Services on Public Satisfaction in Garut Regency - Sutisna, Silmi Khiyarotillah; Muslimah, Sintya; Shafira, Debby; Matondang, Margaretta Vio Della Br; Nurhayati, Dwi (Departemen Ilmu Administrasi FISIP UNHAS, 2026)
This study examines the effect of Digital Population Identity (IKD) service quality on public satisfaction at the Population and Civil Registration Office of Garut Regency, Indonesia. A quantitative approach with an explanatory survey design was employed. Data were collected from 100 IKD users selected through an accidental sampling technique, which was considered appropriate because no comprehensive sampling frame of active IKD users was available. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that IKD service quality has a positive and significant effect on public satisfaction (path coefficient = 0.749; t = 17.398; p < 0.001). The coefficient of determination (R² = 0.560) shows that service quality explains 56.0% of the variance in public satisfaction, while the remaining 44.0% is influenced by other factors outside the research model. The findings suggest that reliable digital services, clear information, responsive service officers, and user-friendly service processes are key determinants of citizens' satisfaction with IKD services. Considering the geographical characteristics of Garut Regency, improving citizens' satisfaction requires not only continuous enhancement of service quality but also context-sensitive strategies, including expanding digital access, strengthening digital literacy, and improving the accessibility of IKD services for communities in remote areas